Ossification of the Vascular Pedicle After Microsurgical Soft Tissue Transfer of the Lateral Upper Arm Free Flap. Issue 6 (December 2019) - Jehn, Philipp; Zimmerer, Rüdiger; Dittmann, Jan; Fedchenko, Mykola; Gellrich, Nils-Claudius; Spalthoff, Simon
Abstract : Abstract: Reconstruction of intraoral defects is one of the main aspects of head and neck cancer treatment. Since the advent of microvascular surgery in this field, free flap tissue transfer has become a common procedure, and various flaps have been described for soft tissue reconstruction. The lateral upper arm free flap is one of the most frequently used flaps for intraoral defect coverage. This article describes ossification of the corresponding vascular pedicle after soft tissue transfer with the lateral upper arm free flap and microsurgical anastomosis in oral cancer treatment. Similar findings in the context of the lateral upper arm free flap have never been reported in the literature; however, it is important for surgeons to know that pedicle ossification can occur. This knowledge may be helpful to avoid erroneous diagnosis of the ossification as a sign of tumor relapse/recurrence as well as to anticipate potential difficulties in the surgical approach in cases requiring reentry of the reconstructed region, for example, in relapse/recurrence of head and neck cancer.